Straw mulching has an enduring positive effect on soil CO2 emissions in a humid plantation - Quan LI; Jiarui FU; Jiahui ZENG; Chao ZHANG; Changhui PENG; Lei DENG; Tingting CAO; Man SHI; Zhikang WANG; Junbo ZHANG; Weifeng ZHANG; Yi ZHANG; et al. (Frontiers of Agricultural Science and Engineering)
Mulching practices substantially affect soil CO2 emissions from agricultural ecosystems. However, the impacts of mulching practices and their enduring effects on soil CO2 fluxes in humid plantations have not been investigated. To address this research gap, a field experiment was conducted in a Moso bamboo (Phyllostachys edulis) plantation in a humid area of China to investigate the effects of various durations of straw mulching and its enduring effects on soil CO2 fluxes and soil organic carbon (SOC). Straw mulching significantly increased the soil CO2 flux by about 18 times relative to the control, mainly due to the increase in soil temperature during the mulching stage. During the period of enduing effect, straw mulching still significantly increased the soil CO2 flux by 230%–270% relative to the control, primarily due to the enhancement of microbial activity resulting from improved soil nutrient contents, demonstrating that straw mulching had an enduring positive impact on soil CO2 flux. Additionally, straw mulching significantly increased SOC by 27%–72% during the mulching and period of enduing effect. These results indicated that straw mulching in plantations in humid regions could be a potential carbon storage strategy by increasing soil carbon content.